2019
DOI: 10.4149/neo_2018_181109n847
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-31-5p may be a potential diagnostic biomarker in nasopharyngeal carcinoma

Abstract: Aberrant expression of miR-31-5p has been detected in various cancers and plays a significant role in tumorigenesis. Low miR-31-5p expression was present in nasopharyngeal carcinoma (NPC) tissues and cell lines and acted as a tumor suppressive miRNA. Currently, circulating miRNAs are emerging as novel biomarkers for the early diagnosis of cancers using a non-invasive method. However, circulating miR-31-5p has rarely been reported in NPC. Therefore, the aim of this study was to explore peripheral blood miR-31-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…However, despite the great advances in medical technology in recent years, such as the application of intensity-modulated radiotherapy and optimized chemotherapy strategies, the detection and treatment of NPC remain challenging [ 9 ]. Epidemiological investigations have shown that although the incidence and mortality rates of NPC have been greatly reduced over the past decade even in endemic areas [ 10 ], the survival rate of NPC patients remains unsatisfactory due to local recurrence and distant metastasis, especially in patients with advanced-stage disease [ 11 ]. Thus, non-invasive, cancer-specific biomarkers for early diagnosis and precision treatment are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the great advances in medical technology in recent years, such as the application of intensity-modulated radiotherapy and optimized chemotherapy strategies, the detection and treatment of NPC remain challenging [ 9 ]. Epidemiological investigations have shown that although the incidence and mortality rates of NPC have been greatly reduced over the past decade even in endemic areas [ 10 ], the survival rate of NPC patients remains unsatisfactory due to local recurrence and distant metastasis, especially in patients with advanced-stage disease [ 11 ]. Thus, non-invasive, cancer-specific biomarkers for early diagnosis and precision treatment are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…The same researchers reported previously that miR-31 was significantly upregulated in OSCC tissues and that it mediated oral oncogenesis by hypoxia pathway regulation [60]. Meanwhile, Yi et al more recently reported that miR-31 level was lower in the whole blood of patients with nasopharyngeal carcinoma (NPC) than in healthy controls and that its reduced expression was associated with local lymph node metastases [37]. In the same study, lower miR-31 expression was associated also with more advanced disease stage and TNM classification.…”
Section: Extracellular Mirnas As Biomarkers Of Hnscc Metastasis Anmentioning
confidence: 99%
“…Recent studies showed that miR-31-5p was downregulated in present in NPC tissues and cell lines, acting as a tumor suppressive miRNA. And circulating miR-31-5p was identified to be a potential novel and non-invasive biomarker for the early diagnosis of NPC (77). The expression levels of tumor-educated platelet miR-34c-3p and miR-18a-5p are upregulated in NPC, which are promising novel liquid biopsy biomarkers for NPC diagnosis (78).…”
Section: Mirnas As Biomarkers and Novel Therapeutic Approaches In Npcmentioning
confidence: 99%